(3GdQjMGf hGdQjYGfs - (3eMeO Hf EHQGgje Hf NjQI, CHh GdbGSe Hf GdehGYjfj GdbQWHj GdETHjdj,J (B564 (3g` s
(3ChdgG (B:s
(3JfJgi HfSH Gdjef ef GdYQH GdYGQHI s
(3fSNI KGdKIs
(3YdjgG Jedc HNW GdUaOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B198s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B477 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B939s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs